Higher Education and Employment : An International Comparative Analysis - Sanyal, Bikas C. (The Falmer Press, 2020)
This book on the relationship between higher education and employment represents the global review or ‘synthesis’ of the experience gained by the International Institute for Educational Planning (Unesco) through a series of 21 national case studies, carried out under the direction of one of its staff members, Bikas C. Sanyal. This research programme was based on joint endeavours between the IIEP and representative national institutions and was spread over a period covering two Medium-Term Plans of the Institute (1978-83 and 1984-89). Throughout this period, the IIEP guided each case study, acting as a catalyst, while national institutions played a more direct and active role